KULI PEREMPUAN INDIA DI PERKEBUNAN TEMBAKAU DELI 1883-1930 - Enggar Istiyana (Universitas Negeri Surabaya, 2022)
The expansion of private plantations in Deli which focuses on tobacco plants requires a large number of workers. Jacob Nienhuys had difficulty finding workers to manage the plantation, so he had to bring in coolies from various regions outside the Dutch East Indies. In historical studies, the theme is about coolies imported from China and Java. Even though the Deli tobacco plantations also brought in coolies from India. In this way, this study aims to identify in detail about Indian coolies, especially female coolies whose role is no less important than coolies imported from China and Java. Using the method of interpreting primary sources obtained from the Digital Collections Leiden University Libraries, this research is a piece of writing capable of addressing the role and position of Indian women coolies in the Deli tobacco plantations, East Sumatra. This research resulted in the fact that Indian coolies also played a role in the Deli tobacco plantations. They decided to migrate to Deli tobacco plantations because of the economic crisis that occurred in India. Hoping to change the fate of the Deli tobacco plantations, the Indian coolies are actually getting back into misery due to the oppression given by the plantation authorities. Keywords: Indian female coolies, East Sumatra Deli, tobacco plantations